Development of a multifunctional catalyst for a ``relay'' reaction - Ganai, Anal Kumar; Shinde, Pravin; Dhar, Basab B.; Sen Gupta, Sayam; Bhagavatula L. V. Prasad (RSC Advances, 2013)
In the area of catalysis, nanoparticles and enzymes are two of the most important systems. By amalgamating the two, we present here proof of the concept that it is possible to prepare a multifunctional catalyst that can carry out a ``relay'' reaction. The catalyst consists of a surface bound enzyme on a metal(core)-silica(shell) nanoparticle architecture. Here the enzyme catalyzes the 1st reaction and the metal nanoparticles act as a catalyst for the 2nd reaction of the product from the 1st reaction. In particular, we have studied the catalytic activity of glucosidase grafted Au@mSiO(2) on 4-nitrophenyl-beta-glucopyranoside, where glucosidase will catalyse the 1st step to generate 4-nitrophenol, which acts as a substrate for the next reduction step which is catalysed by the Au nanoparticles present inside the mesoporous silica shell.

Amphi-functional mesoporous silica nanoparticles for dye separation - Shinde, Pravin; Sen Gupta, Sayam; Singh, Baljeet; Polshettiwar, Vivek; Prasad, Bhagavatula L. V. (Journal of Materials Chemistry A, 2017)
Synthesis of amphi-functional mesoporous silica nanoparticles (similar to 80 nm) by stepwise chemical modifications of outer and inner pore surfaces is reported. These materials display a clear "Janus" like character and are able to selectively and completely separate hydrophobic dyes form a mixture of dyes. Our results clearly suggest a clear partition of more hydrophobic dyes into the pores from a mixture of two dyes. In addition this material displays a remarkable recycling ability for 10 cycles with up to similar to 99% dye removal from water.

Influence of gold nanorods on the structure and photonic bandgap in a twist grain boundary phase with smectic C* blocks - Sahoo, Rajalaxmi; Rao, D. S. Shankar; Hiremath, Uma S.; Yelamaggad, V. C.; Shinde, Pravin; Bhagavatula L. V. Prasad; Prasad, S. Krishna (Journal of Molecular Liquids, 2020)
We describe the first report of the influence of gold nanorods (GNR) on the induced twist grain boundary smectic C* (TGBC*) phase in a binary mixture of achiral bent-core and chiral linear liquid crystals. The GNR concentration-dependent phase diagram of these nanocomposites shows that the thermal range of this twist grain boundary phase having smectic C* blocks phase increases by 50% for an intermediate composition compared to that for the host binary mixture without nanorods. The inclusion of the nanorods is seen to have substantial effect on the structural and photonic bandgap features of the TGBC* phase. For example, the helical periodidty gets altered in all the three dimensions: while those within the block undergo a huge increase, the one which is orthogonal to the blocks, shrinks. The spacing of the square grid pattern arising normal to the TGB helix direction increases for the nanocomposites getting even doubled for a certain composition, a feature evidenced by optical microscopy as well as optical diffraction. Xray diffraction clearly brings out the feature that the presence of GNR alters the thermal character of the transition between the TGBC* and the cholesteric phase. Quantitative analysis of the data indicates that the system would remain in the vicinity of a possible tricritical point, a behavior having wider ramifications to understand the underlying critical phenomenon. Based on the experimental observations, and capturing the essence of the reported adaptive defect core targeting mechanism we propose a model wherein GNRs get confined in the grain boundary region. This feature offers a potential to have periodic and anisotropic plasmonic structure arising out of the synergetic interactions between the metal nanorod and the twisted grain boundary structure. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: 3D photonic bandgap; Gold nanorods; Induced phase; TGBC* phase; Tricritical phenomena

Amphifunctional mesoporous silica nanoparticles with ``molecular gates'' for controlled drug uptake and release - Shinde, Pravin; Prasad, V, Bhagavatula L. (Particle & Particle Systems Characterization, 2021)
It is demonstrated that the uptake and release of hydrophobic drugs/dyes by mesoporous silica nanoparticles (MSN) is critically dependent on the functional groups present on their outer surfaces. For this, amphifunctional MSNs are synthesized, possessing hydrophobic pores and hydrophilic functional groups on the outer surface. Further, the outer surface is modified with a different chain length of molecules, e.g., propargyl alcohol, triethylene glycol, and PEG (2000) via azide-alkyne click chemistry. The effect of these different surface functional groups on uptake of drug/dye is demonstrated with Nile red, proflavine (free base form), and rhodamine 6G. The uptake of these molecules is found to be inversely proportional to the bulkiness of surface functionality. To counter this effect, an alternate method of loading is proposed and demonstrated. Finally, the effect of these different functional groups on the release of loaded drug proflavine is studied, which supports the hypothesis that bulkier outer surface groups also hinder the release of drugs loaded in the porous MSN.
Keywords: drug delivery and release; Mesoporous silica; molecular gating; surface functionalization